A Low‐Profile Circularly Polarized Short Backfire Antenna with High Impedance Surface. Issue 8 (28th May 2013) - Yi, Huan; Qu, Shi‐Wei
ABSTRACT In this article, high impedance surface (HIS) structures are used as a primary reflector of a short backfire antenna to reduce its profile. Crossed dipoles fed by a power divider with 90° phase shift are adopted as an exciter to realize circular polarization. It is demonstrated that the antenna profile can be reduced from 0.6 to 0.3 λ0 by using the HIS structures as a primary reflector. It also achieves a 3‐dB axial ratio bandwidth of more than 25% with a standing‐wave ratio below 2, and the peak broadside gain is around 13.47 dBi with a 3‐dB gain bandwidth of 22.5%. The simulated and experimental results are presented and discussed in the end of this article. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1779–1784, 2013